Study of sungrazing comets with space-based coronagraphs: New possibilities offered by METIS on board Solar Orbiter. Issue 10 (15th November 2015) - Bemporad, A.; Giordano, S.; Raymond, J.C.; Knight, M.M.
Abstract: Thanks to the launch of SOHO in the end of 1995 and to the continuous monitoring of the white light (WL) corona offered by the LASCO coronagraphs, it was discovered that sungrazing comets are much more common than previously thought. More than 2800 comets have been discovered so far over nearly 20 years, hence slightly less than a comet every 2 days is observed by coronagraphs. The WL emission seen by SOHO /LASCO and more recently also by the STEREO /SECCHi instruments provides information not only on the comet orbits (hence on their origin), but also on the dust-tail formation, dust-tail disconnection, occurrence of nucleus fragmentation and nucleus disintegration processes. Very interestingly, a few sungrazing comets have also been observed spectroscopically in the UV by the SOHO UV Coronagraph Spectrometer (UVCS), and the strong emission observed in the Hi Lyman- α 1216 Å line provides direct information also on the water outgassing rate, tail chemical composition, nucleus size, and occurrence of nucleus fragmentation. Moreover, the UV cometary emission provides a new method to estimate physical parameters of the coronal plasma met by the comet (like electron density, proton temperature and solar wind velocity), so that these comets can be considered as "local probes" for the solar corona. Unique observations of comets will be provided in the near future by the METIS coronagraph on board the Solar Orbiter mission: METIS will simultaneously observe the corona in WL and in UV (Hi Lyman- α ), hence it will be a unique instrument capable of studying at the same time the transiting comets and the solar corona. Previous results and new possibilities offered by METIS on these topics are summarized and discussed here.